Acoustic and mechanical characterization of 3D-printed scaffolds for tissue engineering applications. (6th August 2018) - Aliabouzar, Mitra; Zhang, Grace Lijie; Sarkar, Kausik
Abstract: The acoustic and mechanical properties of 3D-printed porous poly-(ethylene glycol)-diacrylate (PEGDA) hydrogel scaffolds were investigated using an ultrasound pulse echo technique on different scaffold microstructures (solid, hexagonal and square pores). Acoustic parameters such as speed of sound, acoustic impedance and attenuation coefficient as well as physical parameters such as the pore structure, effective density and elastic moduli were determined. The results show that microstructure (porosity and pore geometry) plays a crucial role in defining properties of 3D-printed scaffolds, achieving the highest attenuation for the scaffold with hexagonal pores and showing a decrease in sound speed and elastic moduli with increasing porosity. The properties were also found to be similar to those of soft tissues, making PEGDA scaffolds a suitable candidate for tissue engineering applications. To evaluate their cellular performance, adhesion and proliferation of human mesenchymal stem cells (hMSCs) in these scaffolds were investigated. The porous scaffolds performed better than the solid one, recording the highest cell attachment and growth for the scaffold with the square pores.